Melting Hadrons, Boiling Quarks From Hagedorn Temperature to Ultra-Relativistic Heavy-Ion Collisions at CERN : With a Tribute to Rolf Hagedorn - Rafelski, Johann (Springer Nature, 2016)
Nuclear Physics, Heavy Ions, Hadrons; History and Philosophical Foundations of Physics; Particle Acceleration and Detection, Beam Physics; History of Science